2006
DOI: 10.1002/jbm.b.30642
|View full text |Cite
|
Sign up to set email alerts
|

Highly porous 3D nanofiber scaffold using an electrospinning technique

Abstract: A successful 3D tissue-engineering scaffold must have a highly porous structure and good mechanical stability. High porosity and optimally designed pore size provide structural space for cell accommodation and migration and enable the exchange of nutrients between the scaffold and environment. Poly(epsilon-carprolactone) fibers were electrospun using an auxiliary electrode and chemical blowing agent (BA), and characterized according to porosity, pore size, and their mechanical properties. We also investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 33 publications
0
58
0
Order By: Relevance
“…28,30 Although electrospinning provides fine control over nanofiber synthesis, there are some limitations to applications in tissue engineering such as the inability to deposit fibers without an electric field, slow deposition rates, complex synthesis setups, and poor cell penetration within a fibrous network. 13,31 As shown in this and our earlier studies, nanofiber airbrushing provides a solution to many of these limitations. 32 Certain bulk material properties and scaffold morphology, including the Young's modulus, network pore size and porosity were reported to be different between electrospun and airbrushed scaffolds and potentially advantageous for tissue regeneration applications.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…28,30 Although electrospinning provides fine control over nanofiber synthesis, there are some limitations to applications in tissue engineering such as the inability to deposit fibers without an electric field, slow deposition rates, complex synthesis setups, and poor cell penetration within a fibrous network. 13,31 As shown in this and our earlier studies, nanofiber airbrushing provides a solution to many of these limitations. 32 Certain bulk material properties and scaffold morphology, including the Young's modulus, network pore size and porosity were reported to be different between electrospun and airbrushed scaffolds and potentially advantageous for tissue regeneration applications.…”
Section: Introductionmentioning
confidence: 66%
“…Other methods may require unique solvents or specifically designed fiber collecting devices. 4,13,16 On the other hand, airbrushing is a simple, safe, and robust method (composite nanofiber synthesis from various polymers) allowing for more open-pore scaffold structure synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed that cell attachment and proliferation on the surface of biomaterials increases when surface hydrophilicity is increased. 17,23,31,32 To compare the hydrophilicity of the surface of the PCL scaffold before and after surface modifications, the water contact angle of the specimens was measured. The results showed that the hydrophilicity of the surfaces was increased after surface modification, confirming the role of hydrophilic groups (OH and COOH) in increasing the hydrophilicity of surfaces after plasma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, ASCs have been shown to be immune privileged, and more genetically stable in long-term culture, compared to BMSCs. 4 The efficacy of ASCs for tissue regeneration is currently under assessment in clinical trials. 5 Adipose tissue is well established as an easily accessible source of adult mesenchymal stem cells with properties suitable for tissue engineering and cell therapy.…”
Section: Introductionmentioning
confidence: 99%